Calidad del agua para consumo humano en el proceso de captación, tratamiento, distribución y consumo en el cantón La Maná, Provincia de Cotopaxi - Duarte Vera, Félix Rafael (2019)
The research was conducted in the cantón La Maná, Cotopaxi Province, to assess the quality of water for human consumption in the stages of collection, treatment, distribution and consumption. the perception of the public about water quality using surveys and interview the head of the water treatment plant was evaluated. the results of physical-chemical and microbiological characterization Ecuadorian Standard NTE INEN 1108 2014 and World Health Organization (WHO) Ministerial Agreement 097 and EPA were compared. applying water quality and US NSF Dinius indices, and the Colombian ICAUCA index it was determined. The considered physical, chemical and microbiological parameters were: Dissolved Oxygen, Total Coliforms; and Fecal Coliform. The quality of drinking water in the uptake was for ICA-NSF very poor quality for ICA-Dinius contaminated and ICAUCA of inadequate quality, In the treatment is considered to ICA-NSF of very poor quality, ICA-Dinius heavily contaminated and ICAUCA of acceptable quality. Distribution qualified for ICA-NSF good quality, ICA-Dinius ICAUCA excellent quality and optimum quality. Consumption for ICA-NSF, was rated 100% of the points sleazy, For ICA-Dinius 74% of the points of excellent quality, 13% points of acceptable quality and 13% slightly fall contaminated. To ICAUCA all consumption points were considered inadequate quality. It is concluded that the water quality at all stages of collection, treatment and distribution is of poor quality for human consumption in the cantón La Maná, Cotopaxi Province KEYWORDS Quality, potable water supply, collection, treatment, distribution, consumption, surface water.